Thermal sensitivity of Calonectria henricotiae and Calonectria pseudonaviculata conidia and microsclerotia. (4th May 2018) - Miller, Megan E.; Shishkoff, Nina; Cubeta, Marc A.
ABSTRACT: Knowledge of the thermal sensitivity of conidia and microsclerotia is useful for developing plant disease management approaches that deploy heat to inactivate infectious vegetative propagules of fungal pathogens. For boxwood blight disease, heat treatment of cuttings that harbor conidia and microsclerotia would provide a useful management tool for suppressing the pathogenic activity of Calonectria pseudonaviculata (present in the United States) and C. henricotiae (a quarantine pathogen not present in the United States). In this study, we investigated the thermal sensitivity of conidia and microsclerotia of the boxwood blight pathogens C. henricotiae and C. pseudonaviculata treated in water at 45, 47.5, 50, 52.5, and 55 C. For conidia, as time of exposure increased at each temperature, the proportion of germinated conidia decreased. The predicted time required to inactivate 90% of C. pseudonaviculata conidia (LD90 ) decreased as water temperature increased from 45 to 55 C and ranged from 35.4 to 5.6 min, respectively. Inactivation of conidia was dependent on isolate, species of Calonectria, and length of exposure at each temperature tested. Microsclerotia of C. henricotiae and C. pseudonaviculata displayed reduced germination with increasing exposure and higher temperatures of hot water. Microsclerotia of C. henricotiae were significantly more resistant to heat treatment than C. pseudonaviculata at 47.5 and 50 C, whereas microsclerotia of both species were rapidly killed at 55 C.